PERLAKUAN RIZOBAKTERI PEMACU PERTUMBUHAN TANAMAN (RPPT) TERHADAP VIABILITAS DAN VIGOR BENIH SERTA PERTUMBUHAN BIBIT TANAMAN DUA VARIETAS CABAI MERAH (Capsicum annum L.) - Syamsuddin Syamsuddin; Marlina Marlina; Hasanuddin Hasanuddin; M. Abduh Ulim (Prosiding Seminar Nasional Biotik, 2018)
Seed treatments using various chemical substances have been gradually avoided as awarness of their harmful effects on environment and health. The Aim of this Study to determine directional rizobakteri treatment on viability and vigor of seeds of two varieties of Red chilies and to determine directional interaction between varieties of chili and rizobakteri treatment on viability and seed vigor. Chilies seeds inoculated with isolates rizobakteri and germinated with standard procedures. Furthermore sprouts were transferred to plastic pots containing a mixture of soil and growing media compost. Germination was monitored every day up to 14 days, while seedling growth was observed at the age of 6 weeks after transplanting. The results of the study on seed germination phase can be concluded that the response of different varieties to treatment because of the different types rizobakteri rizobakteri used. Isolates rizobakteri Actinobacillus suis and Azotobacter sp effectively improve the viability and seed vigor Arena Red chilies varieties with synchrony value grew 100% and vigor index of 68.33%. While isolates rizobakteri Actinobacillus suis, Azotobacter sp, and P. capacia effectively increases Growing simultaneity for PM999 with the value of each is 93.34%, 95.00%, and 90.00%. At the age of Red chilies seed growth phase 6 after planting, seed treatment uses Red chilies varieties Arena rizobakteri Actinobacillus suis, Azotobacter sp, and P.capacia effectively increases the growth of Red chilies seedlings. In wet weight benchmarks, chili seeds from the seed varieties that are subjected isolates Arena rizobakteri Azotobacter sp varieties of chili seeds and PM999 were treated rizobakteri P.capacia significantly more weight than the seed treatment of other types of rizobakteri other.